2019
DOI: 10.1093/imrn/rnz277
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Dual Volume Deviations of Convex Bodies and Polytopes

Abstract: We establish estimates for the asymptotic best approximation of the Euclidean unit ball by polytopes under a notion of distance induced by the intrinsic volumes. We also introduce a notion of distance between convex bodies that is induced by the Wills functional and apply it to derive asymptotically sharp bounds for approximating the ball in high dimensions. Remarkably, it turns out that there is a polytope that is almost optimal with respect to all intrinsic volumes simultaneously, up to absolute constants. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…From results in [22,21,24,34,35] it follows that as the dimension tends to infinity, the ratio of the best inscribed to best circumscribed approximation of the ball is of the order O(d −1 ln(d)). (The same result holds true for approximation with respect to any intrinsic volume [6]). ) This is some evidence the answer is affirmative.…”
Section: Some Applications and Related Problemssupporting
confidence: 63%
See 1 more Smart Citation
“…From results in [22,21,24,34,35] it follows that as the dimension tends to infinity, the ratio of the best inscribed to best circumscribed approximation of the ball is of the order O(d −1 ln(d)). (The same result holds true for approximation with respect to any intrinsic volume [6]). ) This is some evidence the answer is affirmative.…”
Section: Some Applications and Related Problemssupporting
confidence: 63%
“…When v = 6, there are 4 possibilities for (v, e, f ); Steinitz [42] showed that a polytope in R 3 has v vertices, e edges and f facets if and only if the vector (v, e, f ) satisfies the Euler relation v−e+f = 2 and the inequalities v ≤ 2f − 4 and f ≤ 2v − 4. Hence, if v = 6 then 5 ≤ f ≤ 8 and e = f + 4, so the possible face vectors (v, e, f ) are (6,9,5), (6,10,6), (6,11,7) and (6,12,8). Checking cases, we find that G(6, 12, 8) has the maximum value among the four possibilities.…”
Section: Introduction and Main Resultsmentioning
confidence: 89%
“…We note that approximations of convex bodies in d-dimensional Euclidean space with respect to all intrinsic volume deviations, where the relative position of the polytope and body is not restricted, have recently been studied by Besau et al [2]. They prove asymptotic estimates for best approximations of the unit ball in these deviations measures.…”
Section: Corollary 13 the Minimum Perimeter Deviation Of Convex N-gons From A Given Convex Disc K Is A Concave Function Of N In The Hypermentioning
confidence: 93%
“…)) as δ → 0 + . Thus, by (2), the arc of bd K between o and the positive intersection point of l and bd K has length…”
Section: Proof Of Theorem 12mentioning
confidence: 99%
“…The dual Brunn-Minkowski theory, introduced by Lutwak [40,42], is a variant of classical Brunn-Minkowski theory, which has become a central piece of modern convex geometry, see e.g. [2,7,14,25,26,31,43]. Its starting point is the replacement of Minkowski sum by the so-called radial sum of convex bodies, or more generally, star bodies.…”
Section: Dual Brunn-minkowski Theorymentioning
confidence: 99%